2022
DOI: 10.3390/ma15093111
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medications in Endodontics and Its Application—A Review of Literature

Abstract: Herbal products are gaining popularity in dental and medical practice nowadays due to their biocompatibility, higher antimicrobial activity, antioxidant and anti-inflammatory properties. Herbal medicine has experienced rapid growth in recent years due to its beneficial properties, ease of availability, and lack of side effects. As pathogenic bacteria become more resistant to antibiotics and chemotherapeutic agents, researchers are becoming more interested in alternative products and treatment choices for oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…They are considered to be healthier and more environmentally acceptable. 20 They are easy to obtain and are well accepted by the host with many useful pharmacological actions comparable with synthetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…They are considered to be healthier and more environmentally acceptable. 20 They are easy to obtain and are well accepted by the host with many useful pharmacological actions comparable with synthetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Herbal materials are increasingly valued in dental and medical practice due to their antimicrobial, antioxidant, anti-inflammatory, and biocompatibility properties [ 1 ]. One of these medicinal plants is Moringa oleifera ( M. oleifera ) that belongs to the Moringaceae family and is commonly called horseradish or drumstick tree [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, studies reported its limited action against Enterococcus faecalis and Candida albicans species which are main cause for failure of endodontic treatment (6,8,9) . Plant-derived natural biocompatible agents have strongly gained research interest in the endodontic field due to their markable antibacterial, antiinflammatory and antioxidant properties (10) . These agents have been widely investigated as better, safer, and more potent alternative intracanal medicaments to overcome the drawbacks of CH (11) .…”
Section: Introductionmentioning
confidence: 99%